(untitled) (International Congress on Economics, Management and Business Studies, 2026)
English for Specific Purposes (ESP) has become an essential component of language education in technical colleges, where students require English proficiency tailored to their professional fields. This study examines the key challenges faced in teaching ESP and explores effective strategies to enhance learning outcomes. Drawing on current research and classroom practices, the paper highlights issues such as limited vocabulary knowledge, low student motivation, and lack of specialized materials. It also proposes practical strategies including technology integration, task-based learning, and content-based instruction. The findings suggest that a well-structured ESP approach significantly improves students’ communicative competence and professional readiness.